Detoxification of sugarcane bagasse hydrolysate with different adsorbents to improve the fermentative process - Candido, João Paulo [UNESP]; Claro, Elis Marina Turini [UNESP]; de Paula, Carolina Bilia Chimello [UNESP]; Shimizu, Felipe Lange [UNESP]; de Oliveria Leite, Dilza Aparecida Nalin [UNESP]; Brienzo, Michel [UNESP]; de Angelis, Dejanira de Franceschi [UNESP] (Springer Nature, 2020)
Second generation ethanol has the prospect of becoming an important bioenergy alternative. The development of this technology is associated with the lignocellulosic materials' use, with emphasis on agricultural and agroindustrial by-products from which fermentable sugar can be produced. The acid hydrolysis depolymerizes the hemicellulose releasing mainly xylose. Subsequently, the cellulose can be converted into glucose by enzymatic hydrolysis. However, the acid hydrolysis produces toxic compounds, such as furan derivatives, phenolics, and organic acids, which are harmful to fermentative microorganisms. This study investigated different acid concentrations in the sulfuric acid hydrolysis of sugarcane bagasse (1– 5% m/v) and the use of adsorbents with the prerogative to improve the acid hydrolysate (AH) quality for microbial ethanolic fermentation. Cell growth and fermentative yield of Saccharomyces cerevisiae (PE-2) and Scheffersomyces stipitis (NRRL Y-7124) were evaluated. AH was used as a source of pentoses (17.7 g L−1) and molasses (ME) sugarcane as source of hexoses (47 g L−1). The following adsorbents were used: activated charcoal, clay, hydrotalcite and active and inactive cells of PE-2 and NRRL Y-7124, at concentrations ranging (1 – 8% m/v). Results of cell growth and chemical characterization allowed to select the most effective adsorbents with emphasis for active cells that removed 66% furfural and 51% 5-(hydroxymethyl) furfural) (5-HMF) and alcoholic productivity of 23.5 g L−1 in AH and ME substrates, in the presence of mixed culture. These results indicate the application of active yeast cells in the detoxification of acid hydrolysates of the sugarcane bagasse previously to the fermentation.
Keywords: Adsorbents biologics; Lignocellulose materials; Second generation ethanol; Toxic compounds